2020
DOI: 10.1371/journal.pntd.0008301
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with failing pre-transmission assessment surveys (pre-TAS) in lymphatic filariasis elimination programs: Results of a multi-country analysis

Abstract: Achieving elimination of lymphatic filariasis (LF) as a public health problem requires a minimum of five effective rounds of mass drug administration (MDA) and demonstrating low prevalence in subsequent assessments. The first assessments recommended by the World Health Organization (WHO) are sentinel and spot-check sites-referred to as pre-transmission assessment surveys (pre-TAS)-in each implementation unit after MDA. If pre-TAS shows that prevalence in each site has been lowered to less than 1% microfilaremi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 50 publications
0
17
0
3
Order By: Relevance
“…Prior studies have shown that DA is active against brugian filariasis in Indonesia, and the country’s national filariasis elimination program provides DA as MDA to tens of millions of people each year [ 13 ]. The country makes great progress in its MDA program, but some areas fail pre-transmission assessment surveys or even transmission assessment surveys [ 14 ]. The reasons for such failures may be variable, but in general an improved MDA strategy would be extremely helpful.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that DA is active against brugian filariasis in Indonesia, and the country’s national filariasis elimination program provides DA as MDA to tens of millions of people each year [ 13 ]. The country makes great progress in its MDA program, but some areas fail pre-transmission assessment surveys or even transmission assessment surveys [ 14 ]. The reasons for such failures may be variable, but in general an improved MDA strategy would be extremely helpful.…”
Section: Introductionmentioning
confidence: 99%
“…10 Beberapa wilayah juga melaporkan bahwa masih ditemukan positif antigenaemia pada siswa pada saat evaluasi TAS, baik yang nilainya di bawah cut of point (lulus TAS) maupun yang melebihi cut of point (gagal), di Kabupaten Agam Sumatera Barat TAS-1 (B. malayi), 11 dan di negara lain seperti Bangladesh ditemukan positif pada wilayah endemis tinggi (W. bancrofti). 12 Faktor yang mempengaruhi terjadinya penularan kembali LF (re-transmission) pada wilayah yang telah menyelesaikan POPM diantaranya adalah cakupan POPM yang rendah, 13,14,15,16 penolakan masyarakat karena reaksi efek obat, 17 metode surveilans, lingkungan (agen, vektor, dan reservoar), 18,19,20 faktor sosial demografi, serta perilaku masyarakat (perilaku berisiko dan kepatuhan minum obat). 20,21,22 Burgert-Bucker et al melaporkan bahwa terdapat hubungan yang potensial antara kegagalan pengobatan LF dengan kepadatan penduduk, pengobatan dengan Diethylcarbamazine Citrate (DEC)-Albendazole, POPM 6 tahun atau lebih, terkait pula dengan faktor lingkungan yaitu geografis, curah hujan lebih tinggi, serta indeks vegetasi yang tinggi.…”
Section: Pendahuluanunclassified
“…20,21,22 Burgert-Bucker et al melaporkan bahwa terdapat hubungan yang potensial antara kegagalan pengobatan LF dengan kepadatan penduduk, pengobatan dengan Diethylcarbamazine Citrate (DEC)-Albendazole, POPM 6 tahun atau lebih, terkait pula dengan faktor lingkungan yaitu geografis, curah hujan lebih tinggi, serta indeks vegetasi yang tinggi. 15 Surveilans sangat penting dalam proses pengamatan suatu wilayah endemis LF agar dapat mengurangi kejadian penularan kembali terutama pada wilayah berisiko tinggi.…”
Section: Pendahuluanunclassified
“…Managers may also find that transmission continues at higher-than-expected levels, despite multiple rounds of MDA. 5 As they face these issues, programme managers are increasingly grappling with challenging questions: Who are we not reaching? Why?…”
Section: Introductionmentioning
confidence: 99%